First implication of MIP in bilateral microphthalmia with persistent fetal vasculature. Issue 5 (3rd February 2023) - Santorini, Mélissa; Chesneau, Bertrand; Koskas‐Boublil, Patricia; Metge, Florence; Caputo, Georges; Chassaing, Nicolas; Martin, Gilles; Plaisancié, Julie
Abstract: Persistent fetal vasculature (PFV) is a rare malformative ocular disorder resulting from the failure of the hyaloid vasculature to regress. The severity of the visual impairment is depending on the underlying eye defects, ranging from discreet hyaloid remnants to severe ocular anomalies. Although PFV is generally unilateral, sporadic and idiopathic, a genetic cause has been described in some individuals, especially those presenting with a bilateral and/or syndromic form of PFV. The genes occasionally described in PFV are most often responsible for a wide spectrum of ocular phenotypes such as ATOH7 or NDP, a gene also known to be involved in Norrie disease, a X‐linked vitreoretinopathy with extra‐ocular features. We describe here a patient with an ocular phenotype consisting in non‐syndromic bilateral PFV with cataract and microphthalmia, in whom a recurrent heterozygous de novo MIP disease‐causing variant was detected after using a dedicated 119‐ocular genes panel approach. Defects in the MIP gene are classically associated with dominant non‐syndromic congenital cataract without other ocular malformative features. Thus, this case highlights the value of exploring individuals with PFV, even those with non‐syndromic forms. It also broadens the phenotypic spectrum of the MIP gene, adding new insights into the gene networks underlying PFV pathophysiology, that remains unclear.